Double-carbon-coated bismuth ion doped sodium vanadium phosphate composite material as well as preparation method and application thereof
By doping bismuth ions into the positive electrode material of sodium ion battery and adopting dual carbon coating technology, the problems of low energy density and insufficient electronic conductivity of sodium ion battery are solved, and the electrochemical performance and cyclic stability of the material are significantly improved.
Patent Information
- Application Number
- CN202510083202.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-18
AI Technical Summary
The energy density of sodium ion batteries is lower than that of lithium ion batteries, and the electron conductivity of pure Na3V2 (PO4)3 is lower, resulting in poor high-rate performance, limiting its application in practice.
By doping bismuth ions with larger ion radius and low cost, the volume of vanadium phosphate lattice is expanded, the sodium ion transport channel is expanded, and a three-dimensional conductive network is formed through double carbon (amorphous carbon and graphene) coating technology to improve the conductivity and structural stability of the material.
The reversible specific capacity, cycle performance and rate performance of the positive electrode material of sodium ion battery are significantly improved, and the battery has high conductivity, stable cycle performance and excellent charge and discharge performance.
Smart Images

Figure CN119650667A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a composite material of double-carbon-coated bismuth ions doped with sodium vanadium phosphate, a preparation method and an application thereof. Background Art
[0002] The burning of fossil fuels has led to increasingly severe environmental problems. The development of green renewable energy is urgent. Lithium-ion batteries have the advantages of being renewable and high in energy. However, the large-scale use of lithium-ion batteries has led to a shortage of lithium resources. The physical and chemical properties of sodium and lithium are similar, and their battery structures and compositions are also similar. They are mainly composed of positive electrodes, negative electrodes, separators, electrolytes, current collectors, and positive and negative battery shells. Sodium-ion batteries have certain advantages over lithium-ion batteries in battery manufacturing. Aluminum foil in sodium-ion batteries can be used as positive and negative current collectors at the same time, which not only greatly reduces the manufacturing cost, but also because the density of aluminum is much smaller than that of copper, it can effectively improve the energy density; at the same time, compared with the low reserves and relatively concentrated distribution of lithium resources, sodium resources are not only abundant in reserves but also evenly distributed, so sodium-ion batteries have significant cost advantages. Therefore, the research on sodium-ion batteries is particularly important. However, the standard electrode potential of sodium is slightly higher than that of lithium, so the operating voltage of sodium-ion batteries is lower than that of lithium-ion batteries, which leads to a lower energy density of sodium-ion batteries than that of lithium-ion batteries.
[0003] In sodium-ion batteries, the cathode material is the most critical component. It is mainly responsible for receiving and releasing sodium ions and is the core of the charging and discharging process of sodium-ion batteries. Among the many cathode materials, sodium vanadium phosphate cathode materials have become the focus of research in recent years due to their potential advantages such as high energy density, high power density and excellent stability. However, the electronic conductivity of pure Na3V2(PO4)3 is low, which has a great impact on the electrochemical properties of the material, resulting in poor high-rate performance and other problems, limiting its application in practice. Therefore, in order to make Na3V2(PO4)3 (NVP) materials suitable for large-scale applications, it is necessary to conduct modification research on them. The current main modification methods are: ion doping, carbon coating, material morphology optimization, etc. Although metal ion doping, such as the commonly used potassium ions, magnesium ions, aluminum ions, manganese ions, titanium ions, nickel ions, calcium ions, ruthenium ions, lanthanum ions, zirconium ions and cobalt ions, can improve the bulk ion conductivity and electronic conductivity of NVP, these doping ions commonly used in the prior art have more or less technical defects. For example, manganese ion doping may cause Jahn-Teller structural distortion of the material, thereby deteriorating the electrochemical performance of the material; and metals with ion radii that are too small than the vanadium ion radius are prone to V 3+ / V 2+ Redox reactions become difficult; metals such as ruthenium have the disadvantage of high cost.
[0004] CN114944479B discloses a composite material Na of graphene composite potassium and silicon co-doped sodium vanadium phosphate 3-x K x V2(PO4) 3-y (SiO4) y @rGO, where 0<x<1, 0<y<0.2. The specific preparation method is as follows: dissolve vanadium source, carbon source, sodium source, silicon source, potassium source and phosphorus source in deionized water in turn, and prepare a gel precursor by hydrothermal method. The reaction temperature of the hydrothermal method is 150-200℃ and the reaction time is 15-30h; mix the precursor with graphene, stir, dry in an oven, grind, calcine, and obtain nanoscale Na 3-x K x V2(PO4) 3-y (SiO4) y @rGO particles. First, the patent uses K + Partially replace the Na position in sodium vanadium phosphate with Si 4+ Partially replacing the P position in sodium vanadium phosphate makes doping more difficult. Then, in the method for preparing potassium and silicon co-doped sodium vanadium phosphate graphene composite materials described in the patent, the preparation of the precursor needs to be carried out under high temperature conditions of 150-200°C. At this high temperature, the reaction fluid in the closed reactor will expand in volume and produce a large pressure. There are great safety hazards, and the requirements for actual production equipment and manual operation are relatively high. The control of reaction conditions is relatively complicated, and the influence of parameters such as reaction time, temperature and pressure is relatively large, and the energy consumption is high. In addition, the patent first prepares a gel doped with metal ions, and then mixes the gel with graphene and dries it in an oven. This will cause graphene oxide to stack, thereby affecting the structural integrity of the positive electrode material, resulting in poor rate performance of the battery, low cycle efficiency and other problems. It can be seen that the preparation process steps of this patent are complicated and cannot be applied to large-scale production.
[0005] CN114597381B discloses a method for preparing a sodium vanadium phosphate electrode material of vanadium-position chromium-doped composite graphene, which comprises the following steps: firstly preparing sodium vanadium phosphate by a hydrothermal method; then preparing a slurry by combining the formed sodium vanadium phosphate precursor with graphene oxide; finally performing chromium doping to prepare a chromium-doped composite graphene sodium vanadium phosphate / graphene dry gel; and sintering the dry gel to obtain a chromium-doped composite graphene sodium vanadium phosphate Na3V 2-x Cr x (PO4)3 / graphene electrode material. This patent uses Cr to dope V. The ion radius of chromium ions is smaller than that of vanadium ions. When V is partially replaced by Cr, the bond length of VO bond is reduced and the covalent bond effect is increased, resulting in V 3+ / V 2+The redox reaction becomes difficult, which in turn affects the electrochemical activity of the material.
[0006] Chen Qianhui et al. (Chen Qianhui, Lu Qiuying, Li Rencai, et al. Preparation and electrochemical properties of Bi-doped Na3V2(PO4)2F positive electrode materials [J]. Chemical Technology and Development, 2024, 53(9): 37-41) disclosed a Bi-doped Na3V2(PO4)2F positive electrode material. The bismuth-doped sodium vanadium fluorophosphate obtained in the document has larger agglomerated particles and cannot obtain uniform grains, which is not conducive to Na + The doping matrix provided in the document is sodium vanadium fluorophosphate. When the positive electrode material obtained by doping bismuth ions is used in sodium ion batteries, the discharge capacity at 0.1A / g is only 107mAh / g, and the reversible capacity is low, far from the theoretical capacity. In addition, the document clearly records that the bismuth-doped sodium vanadium fluorophosphate positive electrode material has a low voltage platform at around 3.4V, which shows that the positive electrode material has high voltage characteristics. Summary of the invention
[0007] The purpose of the present invention is to provide a composite material of double-carbon coated bismuth ion doped sodium vanadium phosphate and a preparation method thereof, and to explore the application of the composite material as a positive electrode material in a sodium ion battery. By bismuth ion doping according to the doping amount and double carbon (amorphous carbon combined with graphene double carbon) composite synergy, the obtained composite material is used as a positive electrode material in a sodium ion battery, has a high reversible specific capacity, greatly improves its electrochemical performance, and the battery has high conductivity, stable cycle performance, and excellent charge and discharge performance.
[0008] The technical solution of the present invention is:
[0009] A composite material of double carbon-coated bismuth ion-doped sodium vanadium phosphate, which is Na3Bi x V 2-x (PO4)3 / C@rGO, where 0.05≤x≤0.15.
[0010] Preferably, the double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi x V 2-x (PO4)3 / C@rGO, where 0.1≤x≤0.15.
[0011] When sodium vanadium phosphate is used as a cathode material, there is a problem of low ion diffusion kinetics. The low ion diffusion kinetics will hinder the Na +embedding and extraction processes, thereby weakening the cycle stability of the battery. When studying how to solve the problem of low ion diffusion kinetics of sodium vanadium phosphate positive electrode materials, the present invention innovatively proposes to expand the lattice volume of sodium vanadium phosphate by doping bismuth ions with larger ion radius and low cost rather than reducing the bond length. This can effectively expand the sodium ion transport channel, produce a larger sodium ion diffusion channel, enhance the diffusion kinetics of ions, and help improve the diffusion capacity of sodium ions; stabilize the structure so that it will not produce large volume deformation during the electrochemical reaction. The present invention can achieve the selection of low-cost, green and friendly doping elements without sacrificing material capacity.
[0012] At the same time, the synergistic dual carbon - amorphous carbon and graphene, brings about double coating which further inhibits the agglomeration between particles and forms a three-dimensional conductive network.
[0013] More importantly, the present invention strictly controls the doping amount of bismuth ions within 5%-15% (molar ratio), and uses the double-carbon-coated sodium vanadium phosphate composite material obtained according to the bismuth ion doping amount as a positive electrode material for a sodium ion battery, and the first discharge specific capacity of the battery at 1C can reach 116.88 mAh·g -1 .
[0014] In the present invention, the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material has doped bismuth ions uniformly distributed in irregular sodium vanadium phosphate particles; an amorphous carbon coating layer with uniform thickness is formed on the surface of the sodium vanadium phosphate; and the sodium vanadium phosphate particles are bridged with graphene through the amorphous carbon coating layer.
[0015] Amorphous carbon is deposited on the surface of sodium vanadium phosphate particles, and acts as a bridge between sodium vanadium phosphate doped with bismuth ions and graphene; the bismuth ion doping according to the doping amount cooperates with the co-coating effect of amorphous carbon and graphene oxide double carbon, further improving the conductivity of the material, thereby improving the electrochemical performance of the sodium ion battery positive electrode material.
[0016] In the present invention, the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material has a particle size of 50nm-300nm.
[0017] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the present invention is prepared by 3+ The synergistic effect of doping and double carbon coating makes it into discrete and uniform grains with smaller and more uniform grain size, which greatly shortens the Na + and the transport path of electrons.
[0018] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following steps:
[0019] (1) Preparation of Na3Bix V 2-x (PO4)3 / C@rGO precursor powder:
[0020] First, a vanadium source is added to deionized water, and then heated in a water bath at 50-80° C., and stirred thoroughly until the vanadium source is dissolved.
[0021] Then, after the vanadium source is dissolved, a carbon source, a sodium source, a phosphorus source, and a bismuth source are added in sequence to obtain a mixed solution A; wherein the molar ratio of the vanadium source: the sodium source: the phosphorus source: the bismuth source: the carbon source is 2-x: 3: 3: x: 5, 0.05≤x≤0.15.
[0022] Mixed solution A is heated and stirred in a water bath at 80-100°C. After mixed solution A turns into clear blue, a graphene oxide dispersion with a concentration of 1-8 mg / mL is added to the clear blue mixed solution A, and the mixture is continuously heated in a water bath at 80-100°C and stirred until a gel is formed. The reaction temperature of water bath heating is mild, the process is simple, and it is suitable for large-scale production.
[0023] Finally, the obtained gel was placed at -50 to -20°C and freeze-dried for 24 to 72 hours, and then taken out to prepare Na3Bi x V 2-x (PO4)3 / C@rGO precursor powder.
[0024] The present invention adopts a method of doping bismuth ions and coating graphene oxide by liquid-liquid mixing and continuous water bath heating, which is completed in a one-step method (or one-pot method), and directly generates a gel doped with bismuth ions and coated with graphene oxide in one step; then the gel is freeze-dried to directly obtain Na3Bi x V 2-x (PO4)3 / C@rGO precursor powder.
[0025] The amorphous carbon and graphene oxide double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the above method makes the structure of the graphene oxide sheet more complete and can better preserve the functional groups; at the same time, it can effectively prevent the aggregation of the graphene oxide sheet, and it is not easy to agglomerate, overcome the shortcomings of particle agglomeration and graphene oxide stacking hindering the transmission of electrons and ions in the prior art, and has more excellent dispersion performance; it can significantly improve the electronic and ionic conductivity and the continuity of the electrochemical reaction, solve the defect that it cannot reach the positive theoretical specific capacity as a positive electrode material, help to improve the diffusion capacity of sodium ions, and ensure the good cycle performance of the positive electrode material of the sodium ion battery.
[0026] (2) Preparation of Na3Bi x V 2-x (PO4)3 / C@rGO composites:
[0027] The Na3Bi obtained in step (1) x V 2-x The (PO4)3 / C@rGO precursor powder was first ground and then placed in a porcelain boat, which was placed in the constant temperature zone of a horizontal tube furnace. The temperature was raised to 500-800°C under an argon atmosphere and kept at this temperature for 5-12 h.
[0028] After cooling naturally to room temperature, turn off the argon gas and take it out to obtain Na3Bi x V 2-x (PO4)3 / C@rGO composite material.
[0029] In the present invention, in the preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material, the vanadium source in step (1) is at least one of ammonium metavanadate, vanadium pentoxide and vanadium trioxide.
[0030] The carbon source is at least one of glucose, oxalic acid, citric acid and ascorbic acid. The carbon source is used for sol-gel reaction without causing loss of elements.
[0031] The sodium source is at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate and sodium acetate.
[0032] The phosphoric acid is at least one of ammonium dihydrogen phosphate, sodium dihydrogen phosphate and phosphoric acid.
[0033] The bismuth source is at least one of bismuth chloride and bismuth nitrate. In the actual preparation process, the added bismuth nitrate is hydrated bismuth nitrate, generally bismuth nitrate pentahydrate.
[0034] In the present invention, in the preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material, the graphene oxide (GO) dispersion in step (1) is dispersed by 30kHz-40kHz ultrasonic wave for 30-60min.
[0035] In the present invention, in the preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material, the flow rate of argon gas in step (2) is 80-100 mL / min; and the heating rate is 3-5° C. / min.
[0036] A sodium ion battery positive electrode material, wherein the active material is the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material or the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the above preparation method.
[0037] A sodium ion battery, wherein the active substance of the positive electrode material used in the battery is the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material or the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the above preparation method.
[0038] Furthermore, the electrical performance indicators of the sodium ion battery are as follows: the voltage range is 2.5V-4.0V, the constant current charge and discharge test is carried out at a rate of 1C, and the first discharge specific capacity is 104.9-116.9mAh·g -1 After 300 cycles at 1C, the battery capacity retention rate is 75.5-90%. It can be seen that the composite material is used in sodium ion batteries, and the battery has excellent cycle performance and long life.
[0039] The beneficial effects of the present invention are as follows: the innovative design of the present invention provides a double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to the bismuth ion doping amount, which can effectively expand the sodium ion transport channel and promote ion diffusion after doping bismuth ions according to the doping amount; at the same time, the double carbon is compounded on the surface of the sodium vanadium phosphate particles, which limits the excessive growth of the grain size, prevents the agglomeration between the grains, and further improves the conductivity.
[0040] Compared with pure sodium vanadium phosphate positive electrode material, the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material as a positive electrode material has the following advantages: the electronic conductivity and ionic conductivity are greatly improved, and the initial discharge specific capacity, cycle performance and rate performance of the modified sodium vanadium phosphate positive electrode material are greatly improved.
[0041] In addition, under the premise of using bismuth ions as doping ions and amorphous carbon and graphene co-coating, the innovative design of the present invention adopts a one-step method to prepare bismuth ion-doped double-carbon-coated sodium vanadium phosphate composite materials. The preparation process is simple, the mixing of bismuth ions with sodium vanadium phosphate and graphene oxide is more uniform, the preparation process is safer and easier to operate; the energy consumption is low, the cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the X-ray diffraction pattern of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention.
[0043] Figure 2 This is a scanning electron microscope photograph of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention.
[0044] Figure 3 This is the EDS mapping image of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention.
[0045] Figure 4 This is a battery cycle curve at a low rate of 1C when the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention is used as a positive electrode material in a sodium ion battery.
[0046] Figure 5This is a battery cycle curve at a high rate of 20C when the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention is used as a positive electrode material in a sodium ion battery.
[0047] Figure 6 This is a comparison chart of the rate performance of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared in Example 1 of the present invention when used as a positive electrode material in a sodium ion battery. DETAILED DESCRIPTION
[0048] The raw materials involved in the following examples and comparative examples were all purchased from commercial sources.
[0049] 1. Preparation of button batteries:
[0050] First, the positive electrode sheet is prepared, and the positive electrode active material Na3Bi prepared above is x V 2-x (PO4)3 / C@rGO, conductive carbon black, and polyvinylidene fluoride (PVDF) were added to a mortar at a mass ratio of 8:1:1 and ground for 10-20 minutes to make them uniform. Then, 20-30wt% of the powder mass of N-methylpyrrolidone (NMP) was added and ground for 10-20 minutes to make a uniform slurry. The slurry was then coated on the surface of aluminum foil and dried for 8-12 hours to make a working electrode, and a circular electrode with a diameter of 12 mm was made by a punching machine.
[0051] The button cell was assembled in a glove box in an argon atmosphere, with sodium sheet as the counter electrode material, Whatman diaphragm as the diaphragm between the positive and negative electrodes, and the electrolyte being NaPF6+EC / DEC+5%FEC. EC, DEC and FEC represent ethylene carbonate, diethyl carbonate and fluoroethylene carbonate, respectively. (That is, 1M NaPF6 was dissolved in the PC system, and 5wt% FEC was added for preparation).
[0052] First, place the positive electrode shell on the table, and use tweezers to place the prepared 12mm positive electrode sheet in the middle of the positive electrode shell. Add two drops of electrolyte to fix the positive electrode sheet, then put in the diaphragm, and then use a rubber-tipped dropper to add electrolyte drop by drop to completely soak the positive electrode sheet and diaphragm, then put in the sodium sheet, and finally put in the gasket, shrapnel and negative electrode cover in turn. During the assembly process, be careful not to let the gasket and shrapnel touch the shell, otherwise it will easily cause a short circuit. Then complete the sealing on the sealing machine. During the sealing process, you should also pay attention to the sealing pressure not being too large, otherwise it will cause the sodium sheet to extend and contact the positive electrode shell, thereby causing a short circuit. The sealing pressure can be controlled at around 5MPa.
[0053] Example 1
[0054] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi0.1 V 1.9 (PO4)3 / C@rGO.
[0055] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following specific steps:
[0056] (1) Preparation of Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO precursor powder:
[0057] First, 0.222 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0058] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.0485 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0059] The mixed solution A was heated and stirred at 80° C. in a water bath. After the mixed solution A turned into a clear blue color, 20 mL of a 3 mg / mL graphene oxide dispersion was added to the clear blue mixed solution A. The mixed solution A was continuously heated in a water bath at 80° C. and stirred until a gel was formed.
[0060] Finally, the obtained gel was placed at -50 °C for freeze drying for 24 h and taken out to prepare Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO precursor powder.
[0061] (2) Preparation of Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composites:
[0062] The Na3Bi obtained in step (1) 0.1 V 1.9 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composite material.
[0063] Depend on Figure 1It can be concluded that doping bismuth ions and graphene into sodium vanadium phosphate does not change the shape of the sodium vanadium phosphate peak itself, that is, bismuth ion doping and a small amount of graphene coating do not change the crystal structure of sodium vanadium phosphate.
[0064] Depend on Figure 2 It can be seen that when the molar amount of doped bismuth is 0.1, the obtained particles are more dispersed and the particle size is more uniform, that is, the combined effect of appropriate bismuth ion doping and double carbon coating can inhibit the agglomeration of particles.
[0065] Depend on Figure 3 It can be concluded that the elements are evenly distributed and the successful incorporation of bismuth ions can be demonstrated.
[0066] Depend on Figure 4 It can be concluded that when the double-carbon-coated sodium vanadium phosphate composite material doped with an appropriate amount of bismuth is used as a positive electrode material for sodium ion batteries, its initial discharge specific capacity is improved. When the doping amount is 0.1, the initial discharge specific capacity reaches 116.07 mAh g -1 , close to the theoretical specific capacity of 117 mAh g -1 Therefore, it can be considered that doping with bismuth ions and coating with an appropriate amount of graphene oxide can improve the ionic conductivity.
[0067] Depend on Figure 5 It can be concluded that when the bismuth ion composite graphene-coated sodium vanadium phosphate composite material is used as the positive electrode material for sodium ion batteries, the rate performance of the battery is improved overall. At 1C, 2C, 4C, 6C, 8C, and 10C rates, the discharge specific capacity is 116.07 mAh g -1 、108.84mAh·g -1 、105.01mAh·g -1 、102.37mAh·g -1 、100.18mAh·g -1 、98.74mAh·g -1 At the same time, when the rate returns to 1C, the capacity can still reach 116mAh g -1 , indicating that the modified material has improved structural stability and excellent electrochemical properties.
[0068] Depend on Figure 6 It can be concluded that when the sample doped with 0.1% bismuth ions and coated with graphene is used in sodium ion batteries, the capacity retention rate of the specific capacity at 1C is 86.6% after 300 cycles, while the capacity retention rate of pure NVP after 300 cycles is 53%. Therefore, it can be shown that the modified material has better cycle stability.
[0069] Example 2
[0070] Compared with Example 1, the difference is that in the preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material in Example 2, step (1) prepares Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO precursor powder: The bismuth source added is 0.032 g of bismuth chloride.
[0071] The rest is the same as in Example 1.
[0072] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Example 2 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 116.88 mAh·g at a 1C rate. -1 At the same time, when the rate returns to 1C, the capacity can still reach 116.59 mAh g -1 After 300 cycles at 1C, the capacity retention rate was 89.2%.
[0073] Example 3
[0074] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi 0.05 V 1.95 (PO4)3 / C@rGO.
[0075] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following specific steps:
[0076] (1) Preparation of Na3Bi 0.05 V 1.95 (PO4)3 / C@rGO precursor powder:
[0077] First, 0.228 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0078] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.0243 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0079] The mixed solution A was heated and stirred at 80° C. in a water bath. After the mixed solution A turned into a clear blue color, 20 mL of a 3 mg / mL graphene oxide dispersion was added to the clear blue mixed solution A. The mixed solution A was continuously heated in a water bath at 80° C. and stirred until a gel was formed.
[0080] Finally, the obtained gel was placed at -50 °C for freeze drying for 24 h and taken out to prepare Na3Bi 0.05 V 1.95(PO4)3 / C@rGO precursor powder.
[0081] (2) Preparation of Na3Bi 0.05 V 1.95 (PO4)3 / C@rGO composite materials:
[0082] The Na3Bi obtained in step (1) 0.05 V 1.95 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C·min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.05 V 1.95 (PO4)3 / C@rGO composite material.
[0083] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Example 3 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 104.92 mAh·g at a 1C rate. -1 At the same time, when the rate returns to 1C, the capacity can still reach 103.86mAh·g -1 After 300 cycles at 1C, the capacity retention rate was 75.5%.
[0084] Example 4
[0085] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi 0.15 V 1.85 (PO4)3 / C@rGO.
[0086] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following specific steps:
[0087] (1) Preparation of Na3Bi 0.15 V 1.85 (PO4)3 / C@rGO precursor powder:
[0088] First, 0.216 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0089] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.0728 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0090] The mixed solution A was heated and stirred at 80° C. in a water bath. After the mixed solution A turned into a clear blue color, 20 mL of a 3 mg / mL graphene oxide dispersion was added to the clear blue mixed solution A. The mixed solution A was continuously heated in a water bath at 80° C. and stirred until a gel was formed.
[0091] Finally, the obtained gel was placed at -50 °C for freeze drying for 24 h and taken out to prepare Na3Bi 0.15 V 1.85 (PO4)3 / C@rGO precursor powder.
[0092] (2) Preparation of Na3Bi 0.15 V 1.85 (PO4)3 / C@rGO composite materials:
[0093] The Na3Bi obtained in step (1) 0.15 V 1.85 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C·min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.15 V 1.85 (PO4)3 / C@rGO composite material.
[0094] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Example 4 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 108.84 mAh·g at a 1C rate. -1 At the same time, when the rate returns to 1C, the capacity can still reach 108mAh·g -1 After 300 cycles at 1C, the capacity retention rate was 81.3%.
[0095] Comparative Example 1
[0096] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi 0.2 V 1.8 (PO4)3 / C@rGO.
[0097] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following specific steps:
[0098] (1) Preparation of Na3Bi 0.2 V 1.8 (PO4)3 / C@rGO precursor powder:
[0099] First, 0.211 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0100] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.097 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0101] The mixed solution A was heated and stirred at 80° C. in a water bath. After the mixed solution A turned into a clear blue color, 20 mL of a 3 mg / mL graphene oxide dispersion was added to the clear blue mixed solution A. The mixed solution A was continuously heated in a water bath at 80° C. and stirred until a gel was formed.
[0102] Finally, the obtained gel was placed at -50 °C for freeze drying for 24 h and taken out to prepare Na3Bi 0.2 V 1.8 (PO4)3 / C@rGO precursor powder.
[0103] (2) Preparation of Na3Bi 0.2 V 1.8 (PO4)3 / C@rGO composite materials:
[0104] The Na3Bi obtained in step (1) 0.2 V 1.8 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C·min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.2 V 1.8 (PO4)3 / C@rGO composite material.
[0105] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Comparative Example 1 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 102.43 mAh·g at a 1C rate. -1 .
[0106] Comparative Example 2
[0107] The double carbon-coated bismuth ion-doped sodium vanadium phosphate composite material is Na3Bi 0.01 V 1.99 (PO4)3 / C@rGO.
[0108] The preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material comprises the following specific steps:
[0109] (1) Preparation of Na3Bi 0.01 V 1.99 (PO4)3 / C@rGO precursor powder:
[0110] First, 0.233 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0111] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.00485 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0112] The mixed solution A was heated and stirred at 80° C. in a water bath. After the mixed solution A turned into a clear blue color, 20 mL of a 3 mg / mL graphene oxide dispersion was added to the clear blue mixed solution A. The mixed solution A was continuously heated in a water bath at 80° C. and stirred until a gel was formed.
[0113] Finally, the obtained gel was placed at -50 °C for freeze drying for 24 h and taken out to prepare Na3Bi 0.01 V 1.99 (PO4)3 / C@rGO precursor powder.
[0114] (2) Preparation of Na3Bi 0.01 V 1.99 (PO4)3 / C@rGO composite materials:
[0115] The Na3Bi obtained in step (1) 0.01 V 1.99 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C·min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.01 V 1.99 (PO4)3 / C@rGO composite material.
[0116] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Comparative Example 2 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 101.77 mAh·g at a 1C rate. -1 .
[0117] Comparative Example 3
[0118] The sodium vanadium phosphate composite material is Na3V2(PO4)3. The specific preparation method is as follows:
[0119] 0.234 g of ammonium metavanadate was added to a beaker containing 30 ml of deionized water, and then heated in a water bath at 60°C and stirred thoroughly until the vanadium source was dissolved; after being evenly mixed, 0.961 g of citric acid, 0.12 g of sodium hydroxide, and 0.345 g of ammonium dihydrogen phosphate were added in sequence to obtain a mixed solution A, and then the mixed solution A was heated and stirred in a water bath at 80°C until a gel was formed, and the obtained gel was placed in a -50°C freeze dryer for further drying for 24 hours. After drying, the powder was placed in a tubular furnace and sintered at 700°C for 6 hours to prepare the final sample.
[0120] Depend on Figure 4 It can be concluded that the discharge capacity of pure sodium vanadium phosphate at 1C is only 80.44 mAh g -1 .
[0121] Comparative Example 4
[0122] Compared with Example 1, the difference is that in the preparation method of the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material in Comparative Example 4, step (1) is to place the obtained gel at 80° C. and dry it for 24 hours, and then take it out to prepare Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO precursor powder.
[0123] The rest is the same as in Example 1.
[0124] When the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material obtained in Comparative Example 4 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 100.53 mAh·g at a 1C rate. -1 At the same time, when the rate returns to 1C, the capacity is 99.36 mAh g -1 After 300 cycles at 1C, the capacity retention rate was 72.6%.
[0125] Comparative Example 5
[0126] In comparative example 5, bismuth ions are first doped to obtain a bismuth ion-doped gel, which is then coated with graphene oxide. The details are as follows:
[0127] (1) Preparation of Na3Bi 0.1 V 1.9 (PO4)3 Gel:
[0128] First, 0.222 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0129] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, 0.345 g of ammonium dihydrogen phosphate and 0.0485 g of bismuth nitrate pentahydrate are added in sequence to obtain a mixed solution A.
[0130] The mixed solution A was heated and stirred in a water bath at 80°C until a gel was formed.
[0131] (2) Preparation of graphene-coated Na3Bi 0.1 V 1.9 (PO4)3 Precursor powder
[0132] The Na3Bi obtained in step (1) 0.1 V 1.9 (PO4)3 gel was added to 20 mL of 3 mg / mL graphene oxide dispersion and mixed evenly; then freeze-dried at -50 °C for 24 h and taken out to prepare graphene-coated Na3Bi 0.1 V 1.9 Precursor powder of (PO4)3.
[0133] (3) Preparation of Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composites:
[0134] The graphene obtained in step (2) is coated with Na3Bi 0.1 V 1.9 The (PO4)3 precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composite material.
[0135] When the composite material obtained in Comparative Example 5 is used as a positive electrode material for a sodium ion battery, the first discharge capacity is 97.45 mAh g at a rate of 1C. -1 .
[0136] Comparative Example 6
[0137] Comparative Example 6 adopts the following preparation method:
[0138] (1) Preparation of Na3V2(PO4)3:
[0139] First, 0.222 g of ammonium metavanadate was added to 30 mL of deionized water, and then heated in a water bath at 60° C. and stirred thoroughly until the ammonium metavanadate was dissolved.
[0140] Then, after the ammonium metavanadate is dissolved, 0.961 g of citric acid, 0.12 g of sodium hydroxide, and 0.345 g of ammonium dihydrogen phosphate are added in sequence. After the reaction is completely completed, the solution turns clear blue, and sodium vanadium phosphate Na3V2(PO4)3 solution is obtained.
[0141] (2) Prepare Na3V2(PO4)3 / C@rGO precursor powder.
[0142] First, the sodium vanadium phosphate solution obtained in step (1) is added to 20 mL of a graphene oxide dispersion having a concentration of 3 mg / mL to prepare a slurry.
[0143] Then, 0.0485 g of bismuth nitrate pentahydrate was added to the slurry, and the slurry was heated in a water bath at 80° C. and stirred until a gel was formed.
[0144] Finally, the obtained gel was freeze-dried at -50°C for 24 h and taken out to prepare Na3V2(PO4)3 / C@rGO precursor powder.
[0145] (3) Preparation of Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composites:
[0146] The Na3Bi obtained in step (2) 0.1 V 1.9 The (PO4)3 / C@rGO precursor powder was ground for 20-30 min, then placed in a porcelain boat and placed in a horizontal tube furnace at a constant temperature of 4 °C min under an argon atmosphere with a flow rate of 80 mL / min. -1 The temperature was raised to 700°C at a heating rate of 100 °C and kept at this temperature for 6 h. After cooling naturally to room temperature, the argon gas was turned off and the mixture was taken out to obtain Na3Bi 0.1 V 1.9 (PO4)3 / C@rGO composite material.
[0147] When the composite material obtained in Comparative Example 6 is used as a positive electrode material for a sodium ion battery, the first discharge specific capacity is 96.32 mAh g at a rate of 1C. -1 .
Claims
1. A composite material of double carbon-coated bismuth ion-doped sodium vanadium phosphate, characterized in that: The composite material is Na3Bi x V 2-x (PO4)3 / C@rGO, where 0.05≤x≤0.
15.
2. The double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to claim 1, characterized in that: The composite material is Na3Bi x V 2-x (PO4)3 / C@rGO, where 0.1≤x≤0.
15.
3. The double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to claim 1, characterized in that: The bismuth ions doped in the composite material are uniformly distributed in the irregular particles of sodium vanadium phosphate; an amorphous carbon coating layer with uniform thickness is formed on the surface of the sodium vanadium phosphate; and the sodium vanadium phosphate particles are bridged with graphene through the amorphous carbon coating layer.
4. The double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to claim 1, characterized in that: The particle size of the composite material is 50nm-300nm.
5. The method for preparing the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Preparation of Na3Bi x V 2-x (PO4)3 / C@rGO precursor powder: First, add the vanadium source into deionized water, then heat it in a water bath at 50-80° C. and stir it thoroughly until the vanadium source is dissolved; Then, after the vanadium source is dissolved, a carbon source, a sodium source, a phosphorus source, and a bismuth source are added in sequence to obtain a mixed solution A; wherein the molar ratio of the vanadium source: the sodium source: the phosphorus source: the bismuth source: the carbon source is 2-x: 3: 3: x: 5, 0.05≤x≤0.15; The mixed solution A is heated and stirred in a water bath at 80-100° C., and after the mixed solution A turns into a clear blue color, a graphene oxide dispersion having a concentration of 1-8 mg / mL is added to the clear blue mixed solution A, and the mixed solution A is continuously heated in a water bath at 80-100° C. and stirred until a gel is formed; Finally, the obtained gel was placed at -50 to -20°C and freeze-dried for 24 to 72 hours, and then taken out to prepare Na3Bi x V 2-x (PO4)3 / C@rGO precursor powder; (2) Preparation of Na3Bi x V 2-x (PO4)3 / C@rGO composites: The Na3Bi obtained in step (1) x V 2-x The (PO4)3 / C@rGO precursor powder was first ground and then placed in a porcelain boat, which was placed in the constant temperature zone of a horizontal tube furnace. The temperature was raised to 500-800°C under an argon atmosphere and kept at this temperature for 5-12 h. After cooling naturally to room temperature, turn off the argon gas and take it out to obtain Na3Bi x V 2-x (PO4)3 / C@rGO composite material.
6. The method for preparing the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to claim 5, characterized in that: The vanadium source in step (1) is at least one of ammonium metavanadate, vanadium pentoxide or vanadium trioxide; The carbon source is at least one of glucose, oxalic acid, citric acid or ascorbic acid; The sodium source is at least one of sodium hydroxide, sodium carbonate, sodium bicarbonate or sodium acetate; The phosphoric acid is at least one of ammonium dihydrogen phosphate, sodium dihydrogen phosphate or phosphoric acid; The bismuth source is at least one of bismuth chloride or bismuth nitrate. Optionally, the graphene oxide dispersion in step (1) is dispersed by 30kHz-40kHz ultrasonic dispersion for 30-60min.
7. The method for preparing the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material according to claim 5, characterized in that: The argon gas flow rate in step (2) is 80-100 mL / min; the heating rate is 3-5° C. / min.
8. A sodium ion battery positive electrode material, characterized in that: The active material of the positive electrode material is the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material as described in any one of claims 1 to 4 or the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the preparation method as described in any one of claims 5 to 7.
9. A sodium ion battery, characterized in that: The positive electrode material of the battery is the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material as described in any one of claims 1 to 4 or the double-carbon-coated bismuth ion-doped sodium vanadium phosphate composite material prepared by the preparation method as described in any one of claims 5 to 7.
10. The sodium ion battery according to claim 9, characterized in that: The electrical performance indicators of the sodium ion battery are as follows: the voltage range is 2.5V-4.0V, the constant current charge and discharge test is carried out at a rate of 1C, and the first discharge specific capacity is 104.9-116.9mAh·g -1 ; After 300 cycles at 1C, the battery capacity retention rate is 75.5-90%.
Citation Information
Cited By
Sodium vanadium phosphate composite positive electrode material and preparation method and application thereof
CN120463171A